Please Help Yourself: Queer Preservation and the Uses of the Past. Issue 1 (2nd January 2021) - Anderson, Fiona
Abstract: Throughout 2017, cultural institutions across England and Wales marked the fiftieth anniversary of the partial decriminalisation of sex between men. In this article I explore two projects about public sex and queer space developed in London that year by two contemporary queer artists: Liz Rosenfeld and Prem Sahib. Both employ queer approaches to preservation and archival labour in the face of imminent material erasure, particularly the loss of dedicated queer cultural spaces as a consequence of gentrification, and exhibit a queer disengagement with the public forms of commemoration enacted that year. I consider how Rosenfeld and Sahib's work from 2017, which casts endemic gendered and racialising practices of exclusion and denial in sharp relief, imbues the practices of preservation and archiving with an erotic complexity and an embodied and radical urgency that underscores the precarity of queer spaces and queer archives in contemporary Britain.